Pengaruh pengeluaran pemerintah, investasi dan ekspor terhadap kemiskinan melalui pertumbuhan ekonomi di SUMBAGSEL - Lantari, Oktiza; Amir, Amri; Safri , Muhammad (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
This study aims to examine the direct effect of government expenditure, investment, and exports on economic growth in Sumbagsel during 2000-2021, and the indirect effect of government expenditure, investment, and exports on poverty through economic growth in Sumbagsel from 2000-2021. The data used is secondary data in the form of time series. The method used is path analysis. The results of the study prove that increases in government expenditure, investment and exports directly have a significant effect on increasing economic growth. Increased government expenditure, investment, and exports indirectly have a significant effect on poverty reduction through economic growth. Economic growth can mediate the effect of government expenditure, investment, and exports on poverty.